Molecular Confirmation of Staphylococci Strain’s Identification Isolated in the Hospital and University Center of Brazzaville, Republic of Congo - Léa Gwladys Gangoue; Faust René Okamba Ondzia; Stech Anomene Eckzechel Nzaou; Fils Landry MPELE; Pembe Issamou Mayengue; Fabien Rock Niama; Etienne Nguimbi (International Journal of Clinical Microbiology, 2022)
Bacteria of the genus Staphylococcus are pathogenic Gram-positive bacteria responsible for various infections, including skin suppuration, which can be severe or chronic. The objective of this study was to confirm Staphylococci strain’s identification isolated by bacteriological methods from biological products of CHU-B patients, by molecular methods based on the analysis of the gene coding for 16S rRNA. In total, 30 strains of Staphylococci were isolated including 8 (26.66%) community strains, 22 (73.33%) hospital strains. The products of the amplification of gene fragments encoding 16S rRNA from 10 strains of Staphylococci including 6 strains of Staphylococcus aureus (S. aureus) and 4 Coagulase Negative Staphylococci (CNS) were sequenced. The sequences obtained were subjected to bioinformatics analysis to confirm the results of conventional bacteriological methods. Six (6) S. aureus strains, 2 Staphylococcus haemolyticus strains, 1 uncultured bacterium clone nbw618g09c1, and one Staphylococcus sp. have been identified. These results made it possible to confirm the effectiveness of the molecular method and to show the limits of traditional bacteriological methods in the complete identification of bacteria.
Keywords: Staphylococci